Young Farmers’ Entrepreneurship during the Covid-19 Pandemic - Siti Nurlaela; Epsi Euriga; R. Hermawan; Puri Eka Dewi Fortuna (Universitas Muhammadiyah Yogyakarta, 2023)
Most entrepreneurs have witnessed their businesses fail during the Covid-19 pandemic, and young farmers are no exception. This study revealed the challenges encountered by young farmers during the pandemic and their efforts to address them. Production, capital, marketing, and their effects on income have emerged as significant challenges for them. The participants were young farmers who received business capital through the Young Agricultural Entrepreneurial Development Program (Penumbuhan Wirausaha Muda Pertanian or PWMP). The data were gathered by census method, and 71 young farmers completed and returned the questionnaire via electronic forms. Data were analyzed using a quantitative description. The results unveiled that young farmers encountered production, capital, and marketing issues. Young farmers combated production problems by improving creativity, cooperation, and management. Forming partnerships, developing innovative products, and seeking bank loans were all viable options for addressing the capital shortage. Additionally, marketing concerns were addressed through online marketing, building partnerships, and expanding networks. Besides capital, young farmers required opportunities, mentors, and a supportive environment to succeed as entrepreneurs. The government should establish policies supporting the efforts of young farmers during the pandemic. Moreover, young farmers necessitated training and infrastructure assistance in online marketing.